Microbial ecology‐based engineering of Microbial Electrochemical Technologies. Issue 1 (14th August 2017) - Koch, Christin; Korth, Benjamin; Harnisch, Falk
Summary: Microbial ecology is devoted to the understanding of dynamics, activity and interaction of microorganisms in natural and technical ecosystems. Bioelectrochemical systems represent important technical ecosystems, where microbial ecology is of highest importance for their function. However, whereas aspects of, for example, materials and reactor engineering are commonly perceived as highly relevant, the study and engineering of microbial ecology are significantly underrepresented in bioelectrochemical systems. This shortfall may be assigned to a deficit on knowledge and power of these methods as well as the prerequisites for their thorough application. This article discusses not only the importance of microbial ecology for microbial electrochemical technologies but also shows which information can be derived for a knowledge‐driven engineering. Instead of providing a comprehensive list of techniques from which it is hard to judge the applicability and value of information for a respective one, this review illustrates the suitability of selected techniques on a case study. Thereby, best practice for different research questions is provided and a set of key questions for experimental design, data acquisition and analysis is suggested. Abstract : Microbial ecology is vital for understanding and managing microbial electrochemical technologies. Based on a case study, best practice is provided for the application of microbial ecology techniques and key questions for experimental design, data acquisition and analysis are suggested.